Empirical Evidence for Extended Cognitive Systems. Issue 11 (11th November 2021) - Favela, Luis H.; Amon, Mary Jean; Lobo, Lorena; Chemero, Anthony
Abstract: We present an empirically supported theoretical and methodological framework for quantifying the system‐level properties of person‐plus‐tool interactions in order to answer the question: "Are person‐plus‐tool‐systems extended cognitive systems?" Nineteen participants provided perceptual judgments regarding their ability to pass through apertures of various widths while using visual information, blindfolded wielding a rod, or blindfolded wielding an Enactive Torch—a vibrotactile sensory‐substitution device for detecting distance. Monofractal, multifractal, and recurrence quantification analyses were conducted to assess features of person‐plus‐tool movement dynamics. Trials where people utilized the rod or Enactive Torch demonstrated stable "self‐similarity, " or indices of healthy and adaptive single systems, regardless of aperture width, trial order, features of the participants' judgments, and participant characteristics. Enactive Torch trials exhibited a somewhat greater range of dynamic fluctuations than the rod trials, as well as less movement recurrence, suggesting that the Enactive Torch allowed for more exploratory movements. Findings provide support for the notion that person‐plus‐tool systems can be classified as extended cognitive systems and a framework for quantifying system‐level properties of these systems. Implications concerning future research on extended cognition are discussed.